Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Potential Application of Tamarind Seed Extract as Coagulant Aid in Alum-Based Removal of Polyamide Microplastics - Muhammad Adli Hanif; Naimah Ibrahim; Man Yung Ho; Masitah Hasan; Farrah Aini Dahalan; Nabilah Aminah Lutpi; Norzila Othman; Mohamed Hasnain Isa (International Journal of Environmental Research, 2026)

Sustainable development of novel lime marble dust composite compressed earth blocks: mechanical and durability performance evaluation - Salman Farooq; Zia Ul Islam; Muhammad Isa Khan; Hamza Sajjad (Innovative Infrastructure Solutions, 2026)

Catboost regressor for monsoon rainfall forecasting in Malaysia using atmospheric Beryllium-7 concentration - Mohd Fauzi Haris; Norita Md Norwawi; Mohd Hafez Mohd Isa; Mohd Zaid Hassan Abdul Rahman; Nur Fatini Abdul Ghani; Muhammad Rawi Mohamed Zain (Modeling Earth Systems and Environment, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

Porosity estimation and reservoir characterisation in Central Luconia Miocene carbonates: integrating systematic review with deep learning analysis of thin sections - Abdulrahman Danlami Isa; Haylay Tsegab Gebretsadik; Abdulrahman Muhammad; Hassan Salisu Mohammed; Mohammed Gali (Arabian Journal of Geosciences, 2026)

Recent advances in vaccination strategies against acute hepatopancreatic necrosis disease (AHPND) in shrimp for sustainable aquaculture industry: A comprehensive review - Tijani Isa; Riyanto Teguh Widodo; Suzita Mohd Noor; Nur Asyura Nor Amdan; Zulhisyam Abdul Kari; Norhidayah Mohd Taufek; Fathiah Mohamed Zuki; Alias Abdullah; Subha Bhassu; Zarif Mohamed Sofian; Sagir Mustapha; Didi Erwandi Mohamad Haron; et al. (Fish & Shellfish Immunology, 2026)

Development and validation of SR-DISVAXFIC: A mobile phone application for estimating the herd-level financial impact of small ruminant diseases and the potential benefits of vaccination in the field - Megan E. Rawlins; Adeyinka J. Adedeji; Victoria I. Ifende; Sandra I. Ijoma; Rebecca B. Atai; Joel Y. Atuman; Gambo Panzam; Haruna W. Gotom; Idris H. Adamu; Anas U. Musa; Isa M. Sani; Paul Adamu; et al. (Preventive Veterinary Medicine, 2026)

Ficus deltoidea Preserves Hippocampal Neuronal Integrity and Redox Balance in Oxidative Stress-Driven Alzheimer’s Disease-Like Rat Model - Alhaji Modu Bukar; Che Mohd Nasril Che Mohd Nassir; Michael Ayuba; Sushmita Devi Manoharan; Abdulhamid Sani Usman; Babagana Isa Umar; Zaw Myo Hein; Mohamad Aris Mohd Moklas; Muhammad Zulfadli Mehat; Hafizah Abdul Hamid (Molecular Neurobiology, 2026)

Porosity estimation using deep learning and ImageJ: Implications for reservoir characterization in Central Luconia Miocene carbonates - Abdulrahman Danlami Isa; Haylay Tsegab Gebretsadik; Abdulrahman Muhammad; Hassan Salisu Mohammed; Ibrahim Muhammad Kurah; Adamu Kamaliddeen Salisu (Marine and Petroleum Geology, 2025)

DFT insights into the adsorption mechanisms of environmental gases on 2H-WTe₂ for potential sensing applications - Saleh S. Alarfaji; Niaz Ahmad; Swera Khalid; Farooq Aziz; Tahir iqbal; Muhammad Isa Khan (Journal of Environmental Chemical Engineering, 2025)

Evaluation of calcium-carboxylate MOFs (Ca-MOFs) as promising adsorbents for simultaneous adsorption of endocrine disruptors compounds (EDCs) from aqueous solutions - Muhammad Qusyairi Jori Roslan; Ahmad Zaharin Aris; Fahren Fazzer Sukatis; Azim Haziq Zainuddin; Abdul Rahman Mohd Basyaruddin; Hong Ngee Lim; Noorain Mohd Isa (Journal of Environmental Management, 2025)

DFT investigation of pristine and li-functionalized TiS2 monolayers for toxic gas sensing applications - Zunaira Saleem; Saleh S. Alarfaji; Humaira Shaheen; Abdul Majid; Muhammad Isa Khan (Journal of Environmental Chemical Engineering, 2025)

Systematic study on the relationship between Beryllium-7 concentration with dynamics of northeast monsoon activity - Mohd Fauzi Haris; Norita Md Norwawi; Mohd Hafez Mohd Isa; Muhammad Rawi Mohamed Zin; Mohd Zaid Hassan Abdul Rahman; Haizum Ruzanna Sahar; Azlai Ta'at (Journal of Environmental Radioactivity, 2025)

Arsenic speciation using HPLC–ICP–MS in white and brown rice and health risk assessment - Raneesha Navaretnam; Ahmad Zaharin Aris; Muhammad Faizan A. Shukor; Mohd Nor Faiz Norrrahim; Victor Feizal Knight; Teen Teen Chin; Noorain Mohd Isa; Ley Juen Looi (Environmental Geochemistry and Health, 2025)

Valorization of oil palm Biomass: Investigating ChCl:Lactic Acid deep eutectic solvents for efficient furfural production - Muhammad Fakhrul Syakir Bahazin; Nur Ismah Amalin Mohd Isa; Nur Anis Natasha Mohd Azlan; Mohd Razealy Anuar; Khairul Faizal Pa'ee; Tau-Len Kelly Yong (Biomass and Bioenergy, 2025)

Evaluation of the shallow hydrothermal system in Jaboi Volcano based on the combination of remote sensing and geophysical measurements - Muhammad Yanis; Muhammad Isa; Nasrullah Zaini; Faisal Abdullah; Muksin Umar; Marwan; Cutti Zahrati; Bondan Galih Dewanto; Riski Ananda; Azman Abdul Ghani (Geosciences Journal, 2025)

Impact of solar powered mini water systems on WASH service delivery among schools in Pader district, Uganda - Patrick Kagurusi; Muhammad Luyima; Hajra Mukasa Comfort; Elizabeth Nagawa; Isa Sematimba; Anthony Egau Okar; Maureen Nankanja (International Journal of Hygiene and Environmental Health, 2025)

Polycyclic aromatic hydrocarbons (PAHs) occurrences in water bodies, extraction techniques, detection methods, and standardized guidelines for PAHs in aqueous solutions - Rana Muhammad Mubeen Muhsin; Teh Sabariah Binti Abd Manan; Joseph Bidai; Muhammad Sarfraz Ahmad Mangat; Zarimah Mohd Hanafiah; Adel Gohari; Naveed Ahmad; Farooq Ahmad; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala'in; et al. (Science of The Total Environment, 2025)

Impact of urea-molasses treated wheat straw levels in total mixed rations on growth and nutrient digestibility in Azikheli buffalo calves - Haroon Ur Rashid; Taimoor Khan; Anwar Ali Turi; Muhammad Abbas; Kalim Ullah; Isa Fusaro; Giovanni Buonaiuto; Damiano Cavallini (Tropical Animal Health and Production, 2025)
This study investigates the impact of urea molasses-treated wheat straw on growth performance and nutrient digestibility in Azikheli buffalo male calves. A longitudinal experiment was conducted on sixteen calves, randomly assigned to four experimental dietary treatments ( n = 4 per group). The experimental diets included a control group (U0) with untreated wheat straw and three groups where urea molasses-treated wheat straw replaced 33% (U33), 66% (U66), or 100% (U100) of the straw in the total mixed ration. Results indicated that increasing the proportion of urea-treated wheat straw from 0 to 100% led to significant improvements in dry matter intake (from 2931 to 4034 g/day) and organic matter intake (from 2596 to 3623 g/day). Digestibility of dry matter, organic matter, crude protein, and crude fiber also followed an increasing trend, reaching 77.42%, 81.21%, 87.10%, and 60.22%, respectively, at the highest urea-treated wheat straw level. Furthermore, weight gain was significantly greater in calves fed 100% urea-treated wheat straw, followed by those in the U66, U33, and U0 groups. Feed conversion efficiency improved substantially in the U100 and U66 groups than U33 and U0. These findings suggest that incorporating higher levels of UMTWS in total mixed rations enhances nutrient digestibility, promoting superior growth performance and feed efficiency in Azikheli buffalo calves.

Optimisation of selected plasticiser compounds adsorption on calcium-carboxylate-based linker (Ca-H2BDC) using response surface methodology - Muhammad Qusyairi Jori Roslan; Ahmad Zaharin Aris; Muhammad Raznisyafiq Razak; Muhammad Rozaimi Mohd Zaki; Abdul Rahman Mohd Basyaruddin; Hong Ngee Lim; Noorain Mohd Isa; Muhamad Aidilfitri Mohamad Roslan (Journal of Water Process Engineering, 2024)

Laboratory-based assessment of geotechnical characteristics of organic waste-amended soil for landfill biocover - Suaidah Rahim; Mohamed Hasnain Isa; Shahriar Shams; Muneerah Jeludin; Ena Kartina Abdul Rahman; Rozeana Hj Md Juani; Muhammad Raza Ul Mustafa; Teh Sabariah Abd Manan; Ahmad Hussaini Jagaba (Environmental Science and Pollution Research, 2024)

Impacts of installation methods on the thermal performance of lightweight exterior cladding panels incorporating PCM: An experimental evaluation - Zeyad Amin Al-Absi; Mohd Isa Mohd Hafizal; Muhammad Asif; Aasem Alabdullatief; Mazran Ismail (Building and Environment, 2024)

Nanoscale zero-valent iron (NZVI) intercalated MXene (Ti3C2Tx) for removal of polycyclic aromatic hydrocarbons in wastewater - Muhammad Raza Ul Mustafa; Hifsa Khurshid; Mohamed Hasnain Isa (Journal of Environmental Chemical Engineering, 2024)

Identification of potential inhibitors of shikimate kinase from Mycobacterium tuberculosis using in silico approach - Mustafa Alhaji Isa; Mohammed Mustapha Mohammed; Muhammad Musa Ibrahim; Falmata Audu Gubio; Fatimah Buba; Somia Shehzadi (Journal of Proteins and Proteomics, 2024)

Vertical electrical sounding for revealing the groundwater resources in the geothermal spring of Jaboi volcano - Muhammad Yanis; Nasrullah Zaini; Faisal Abdullah; Muhammad Isa; Marwan Marwan; Syafrizal Idris; Andri Yadi Paembonan; Riski Ananda; Muzakir Zainal; Azman Abdul Ghani; Deni Saputra (Acta Geophysica, 2023)

Microplastic Pollution in Freshwater Sediments: Abundance and Distribution in Selangor River Basin, Malaysia - Muhammad Rozaimi Mohd Zaki; Fahren Fazzer Sukatis; Muhammad Qusyairi Jori Roslan; Noorain Mohd Isa; Fatimah Md Yusoff; Ahmad Zaharin Aris (Water, Air, & Soil Pollution, 2023)

Influential biosorption of lead from aquatic solution using Escherichia coli/carbon nanofibers - Imran Khan Rind; Ahmet Sarı; Mustafa Tuzen; Muhammad Farooque Lanjwani; Isa Karaman; Tawfik A. Saleh (Environmental Nanotechnology, Monitoring & Management, 2023)

In silico molecular docking and molecular dynamic simulation of potential inhibitors of 3C-like main proteinase (3CLpro) from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) using selected african medicinal plants - Mustafa Alhaji Isa; Adam Mustapha; Sahar Qazi; Khalid Raza; Ibrahim Alkali Allamin; Muhammad M. Ibrahim; Mohammed M. Mohammed (Advances in Traditional Medicine, 2022)

A preliminary studies to assess public knowledge of beach safety in east coast Malaysia - Nur Adawiyah Mohammed Isa; Muhammad Zahir Ramli; Siti Fairuz Che Othman; Muhammad Zubir Yusof (Natural Hazards, 2021)

Detection of ploidy and chromosomal aberrations in commercial oil palm using high-throughput SNP markers - Ting Ngoot-Chin; Muhammad Azwan Zulkifli; Eric van de Weg; Noorhariza Mohd Zaki; Norhalida Mohamed Serdari; Suzana Mustaffa; Mohd Isa Zainol Abidin; Nik Shazana Nik Mohd Sanusi; Marinus J. M. Smulders; Eng Ti Leslie Low; Maizura Ithnin; Rajinder Singh (Planta, 2021)

Artificial Neural Network (ANN) for Modelling Adsorption of Lead (Pb (II)) from Aqueous Solution - Taimur Khan; Muhammad Raza Ul Mustafa; Mohamed Hasnain Isa; Teh Sabariah Binti Abd Manan; Yeek-Chia Ho; Jun-Wei Lim; Nur Zulaikha Yusof (Water, Air, & Soil Pollution, 2017)

Effect of resveratrol and environmental enrichment on biomarkers of oxidative stress in young healthy mice - Mustapha Shehu Muhammad; Rabiu Abdussalam Magaji; Aliyu Mohammed; Ahmed-Sherif Isa; Mohammed Garba Magaji (Metabolic Brain Disease, 2017)

Prediction of pore-water pressure response to rainfall using support vector regression - Nuraddeen Muhammad Babangida; Muhammad Raza Ul Mustafa; Khamaruzaman Wan Yusuf; Mohamed Hasnain Isa (Hydrogeology Journal, 2016)

Isolation and phylogenetic analysis of caprine Orf virus in Malaysia - Ashwaq Ahmed Abdullah; Muhammad Farid Bin Ismail; Krishnan Nair Balakrishnan; Jamilu Abubakar Bala; Homayoun Hani; Yusuf Abba; Mohd Kamaruddin Awang Isa; Faez Firdaus Jesse Abdullah; Siti Suri Arshad; Zeenatul Allaudin Nazariah; Rasedee Abdullah; Noordin Mohamed Mustapha; et al. (VirusDisease, 2015)

Effect of pH on the static adsorption of foaming surfactants on Malaysian sandstone - Muhammad Mushtaq; Isa M. Tan; Umer Rashid; Muhammad Sagir; Mudassar Mumtaz (Arabian Journal of Geosciences, 2015)